Asia-Pacific Countries with Special Needs Development Report 2018 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2018)
This publication discusess issues of interest for the region’s countries with special needs. It offers an analytical background for the multidimensional linkages between peace and sustainable development and attempts to categorize policy recommendations that support the 2030 Agenda and maintain peace and prevent conflict. It focuses on countries with special needs and the structural development challenges they face, in combination with their limited capacities and resources, which make them particularly vulnerable to conflict. It provides recommendation on policies that could be strengthen the nexus between development and peace through further research on the underlying causes of vulnerability of countries in the region.